Almost sure local central limit theorem for sample range. Issue 3 (1st February 2017) - Zang, Qing-Pei
ABSTRACT: Let { Xn ; n ⩾ 1} be a sequence of independent and identically distributed random variables. The sample range is . In this paper, we derive, under some mild assumptions, an almost sure local central limit theorem for sample range.